The Effect of Circ and Csr-Based Role Playing Game on Students’ Reading Comprehension - Wicaksono, Firman; Rukmini, Dwi; Yuliasri, Issy (English Education Journal, 2018)
This study presented the experimental research finding which its This study presented the experimental research finding which its objectives were to identify the effect of Cooperative Integrated Reading and Composition (CIRC)-based Role Playing Game and Collaborative Strategic Reading (CSR)-based Role Playing Game (RPG) on reading comprehension of the students with different learning styles. The subjects were 56 students from two classes of vocational High School in Pati with visual and auditory learning style. The two classes were randomly selected to be an experimental group I (CIRC-based RPG) and an experimental group II (CSR-based RPG). The data were obtained from questionnaire and pretest/ posttest. The findings revealed that the students of the experimental group I perform better on reading skill than the experimental group II; however it was not significant. The data showed CIRC- based RPG and CSR- based RPG were effective in improving students’ reading comprehension. Then, students’ learning styles, visual and auditory students, did not differ significantly from one another in their effect on the students’ reading comprehension (F<4.03 and p: .05). Finally, it was found that there was no interaction among teaching techniques, students’ learning style and reading comprehension.